Analysis of the epidemiological burden of acne vulgaris in China based on the data of global burden of disease 2019 - Wang, Yan; Xiao, ShengXiang; Ren, JianWen; Zhang, YanFei (Frontiers in Medicine, 2022)
Acne vulgaris is a chronic, inflammatory skin disease, which has brought an increasing disease burden to patients and society. But there is no systematic study on the disease burden and social development of acne vulgaris in China. This study aimed to analyze the epidemiological burden and trend of acne vulgaris in China from 1990 to 2019 based on the data in the global burden of disease 2019 (GBD 2019). The number of incidences/illnesses, age-standardized incidence/prevalence rates, disability-adjusted life years (DALYs), and DALY rate of acne vulgaris in China from 1990 to 2019 were obtained from the GBD 2019 to evaluate the epidemiological trends and age-period-cohort trends. The associations between disease burden and social development degrees were analyzed using a sociodemographic index. In 2019, the age-standardized prevalence and incidence of acne vulgaris in China were both at low levels in the world. From 1990 to 2019, the prevalent cases and incident cases of acne vulgaris in China rose firstly and then fell (peaked in 2005 and 2003, respectively), and the age-standardized prevalence/incidence/DALY rates showed growth trends continuously. The prevalence of acne vulgaris peaked in the 15–19 age group while the incidence peak age was 10–14 years old and there was an obvious gender difference, females were higher than males. With the increase of sociodemographic index (SDI) value, the morbidity of acne vulgaris showed a linear growth trend (P < 0.05). From 1990 to 2019, the disease burden of acne vulgaris is increasing in China, which is correlated with social and medical development. Active research on the epidemiological data of acne vulgaris and its relationship with the level of social development is important for both the diagnosis and treatment of acne vulgaris and for the development of health policies.